Modeling in microelectronics at microwave/millimeter-wave frequencies and innovative circuit design - Lim, Hong Yi (2015)
The advancement in microwave theories along with fabrication capabilities of modern foundries in terms of material processing and improved microelectronic devices have brought about unprecedented MMIC designs in terms of its size, power and frequency of operation. Through the discussion of active device modeling and innovative circuit design, this research work hopes to exploit the advancements in microelectronic devices and to achieve breakthrough in terms of circuit design methods and circuit performances. In this thesis, the empirical modeling for an AlGaN/GaN HEMT device capable of high power performance is described. The modeling for an AlGaN/GaN HEMT was selected due to the material characteristics of the device but the modeling procedures and empirical formulations are not limited to GaN based devices. The research work covers the modeling process from data acquisition to the characterization of the device using empirical formulas and the implementation of the proposed model in circuit simulators. From the bias independent small-signal linear model, the extrinsic parasitic parameters are extracted and subsequent modeling work is performed on the evaluated intrinsic device performance. Due to the large biasing voltages that can be applied on the HEMT device, emphasis was given to ensure that simulation will not result in errors and the characteristics are adequately modeled. A charge modeling method applied on the model allows the charge model to model the symmetrical nature of the HEMT device. The active current which represents a major non-linearity of the HEMT is modeled with a proposed new current model to more accurately capture the characteristics at critical regions of the device characterization. The forward diode current model is also described and a similar equation form is adopted for the breakdown current model.